ADOLESCENT LEARNERS’ PERCEPTIONS OF ASSESSING SPEAKING AND WRITING SKILLS – CRITICAL INCIDENT ANALYSIS - Anna Czura (Neofilolog, 2019)
Learners’ perceptions of teacher assessment practices shape a unique classroom assessment environment that affects learners’ willingness to engage in a task and motivation to learn (McMillan & Workman, 1998). Still, there has been limited research on learners’ perceptions of classroom and high-stakes assessment. This article outlines a study exploring adolescent learners’ perceptions of the speaking and writing assessment they experience in the English classroom. The Critical Incident Technique (CIT) was used to examine both positive and negative instances of oral and written assessment. During oral interviews, the learners reported and elaborated on the assessment experiences they personally perceived as particularly important, memorable and influential. The transcriptions of the interviews were content analysed in order to identify the properties of oral and written assessment that appeared salient to adolescent learners. The study indicates that the participants held predominantly positive views of oral and written assessment, emphasising such aspects as authenticity of assessment, freedom of expression and fair grading. It is worrying, however, that learners are not always provided with clearly articulated assessment criteria and that oral assessment is visibly neglected in the classroom.